2001
DOI: 10.1016/s1388-9842(01)00186-6
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced ST‐elevation is related to left ventricular dysfunction but not to myocardial viability in patients with healed myocardial infarction

Abstract: Background: Exercise-induced ST-segment elevation was proposed as a marker of myocardial viability after a recent myocardial infarction. Aims: The aim of this study was to evaluate whether exercise-induced ST segment elevation is related to viability or to left ventricular dysfunction in patients with history of old Q wave myocardial infarction. Methods: Fifty Ž . patients 43 men, age 57 " 11 years were studied 31 " 49 months after a Q wave myocardial infarction. They all underwent stress, reinjection-redistri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…During the past decade, however, ST‐segment elevation in Q‐wave leads has attracted clinical attention concerning its diagnostic potential for residual ischemia in MI patients 24 . Some investigators reported that ST‐segment elevation in Q leads was a highly specific marker of residual ischemia, 25,26 while others presented negative evidence 27–29 . Combination of exercise‐induced ST‐segment elevation and pseudonormalization of negative T waves 30 or ST‐segment depression 31 have been reported to indicate residual ischemia within the infarct‐related area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, however, ST‐segment elevation in Q‐wave leads has attracted clinical attention concerning its diagnostic potential for residual ischemia in MI patients 24 . Some investigators reported that ST‐segment elevation in Q leads was a highly specific marker of residual ischemia, 25,26 while others presented negative evidence 27–29 . Combination of exercise‐induced ST‐segment elevation and pseudonormalization of negative T waves 30 or ST‐segment depression 31 have been reported to indicate residual ischemia within the infarct‐related area.…”
Section: Discussionmentioning
confidence: 99%
“…24 Some investigators reported that ST-segment elevation in Q leads was a highly specific marker of residual ischemia, 25,26 while others presented negative evidence. [27][28][29] Combination of exercise-induced ST-segment elevation and pseudonormalization of negative T waves 30 or ST-segment depression 31 have been reported to indicate residual ischemia within the infarct-related area.…”
Section: Discussionmentioning
confidence: 99%